Fracture grouting and geonails for soft soil tunnelling. Issue 2 (3rd April 2019) - Cheng, Y. M.; Au, S. K.; Wong, H.
ABSTRACT: To stabilise the tunnel faces and slopes in soft clay for the Airport Link construction in Australia, fracture grouting and glass fibre-reinforced plastic (GFRP) soil nails are proposed for the soil improvement as well as ease of handling. The compensation caused by the fracture grouting and the gain in strength due to consolidation as well as the geonail have stabilised the soft clay during construction. Only a small amount of ground settlement during soft clay box-jacking operation is generated so that the railway traffic above the embankment can be maintained without interference. The design method of the fracture grouting ground improvement study for this difficult project is discussed in this paper. Extensive laboratory and field tests were employed to verify the design assumptions and to fine-tune the ground improvement studies. The success of this project in poor ground conditions results from combined efforts of extensive field tests, an improved ground improvement design method and a realistic numerical analysis to assess the unstable/highly stressed zones for the placement of soil reinforcement.